Meaning and Making: Laying the Groundwork for Community-Based Research-Creation (LEARNing Landscapes, 2023)
Research-creation practices have long consulted the public in the process of research, yet the act of making often rests in the hands of the individual researcher. This paper proposes a more integrated and collaborative framework for arts-based researchers and educators called Community-Based Research-Creation, which extends the collaborative logic of oral history into the realm of creation by encouraging art educators to develop focused and prolonged workshops and classes with community. I draw from my own practice as a community art teacher working primarily with adults and propose methods and frameworks for developing community-engaged studies using artworks.
Keywords: community-based art education; arts-based research; research-creation; community making; community pedagogy; community-based research-creation